Intrapreneurship amongst unit nurse managers at public hospitals - Letsie, Thandiwe; Van der Merwe, Anita; Botha, Delene (International Journal of Advanced Nursing Studies, 2014)
AIM: To improve conceptual clarity of the term commonly used in business intrapreneurshipâ€, as it has potential for application in the public health care facility.Background: Intrapreurship is a term commonly used in the business world. However, the term is poorly understood within the nursing fraternity, yet there is potential for application in health care facilities. The daunting challenges facing public care organizations call for incorporation of innovative initiatives embodied within intrapreneurial principles. Therefore, the intrapreneurial unit nurse managers as frontline runners in the delivery of health care services are well positioned to influence the accomplishment of positive health outcomes.Design: A concept analysis.Data sources: The meaning of intrapreneurship was searched from different sources inclusive of dictionaries and thesauri. Literature from a range of disciplines was explored to better understand the concept, this included; business economics, psychology, and public management. Similarities and differences with other similar concepts such as â€˜entrepreneurshipâ€™ were also established. Other surrogate terms that are usually confused with intrapreneurship, were also isolated and defined so that more clarity on the concept of interest can surface.Review method: Walker and Avantâ€™s methodology guided the concept analysisDiscussion of findings: Attributes which best define intrapreneurship include; innovation, creativity and risk taking. Created model, borderline and contrary cases brought clarity on the expected intrapreneurial behavior by a unit nurse manager. The antecedents of intrapreneurship were categorized into three aspects namely; the external environment, intra-organizational and the individual factors. Consequences of intrapreneurship include; new business venture, innovative initiatives leading to self- renewal. The empirical referents of an intrapreneurial organization include aspects such as; effective cost management strategies, positive response to change, application of new skills and client/employee satisfaction.